Inner Conflicts of Leading Female Characters in Sudha Murthy’s ‘Dollar Bahu’: Understanding the Inner Conflict and Social Influence on Female Characters in Sudha Murthy's 'Dollar Bahu' (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The characters of Sudha Murthy’s novels are drawn from everyday lives. The attitude and trait of her characters is highly influenced by social conformity, where the individual’s behavior has been paramount from the early stages of personality development. Karen Horney and Harry Stack Sullivan focus on women and social context and inter personal relationship. A research on personality and its related issues can be possible only with the understanding of other social sciences. As anxiety is a part of personality, it influences the overt behavior of the characters under discussion – Gowramma, Vinutha and Jamuna from Sudha Murthy’s novel “Dollar Bahu”. This paper attempts to bring out the back ground of Sudha Murthy’s characters and the setting for their spontaneous reactions and the effects of the character’s personality upon her relationship to the society. It also considers personality as the source of insight and tries to discuss the personality of the character to the basic social concepts, emotion and thoughts.